2014
DOI: 10.9790/0853-13833742
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and Nutritional Status of School Going Adolescent Girls in a Semi Urbon Area of West Bengal, India

Abstract: Adolescence is a journey from the world of childhood to the world of adulthood. In India adolescents constitute 21.4% of the population that comprises one-fifth of the total population. The health and nutritional status of the children is an index of the national investment in the development of future manpower. Thus present study was undertaken to assess the nutritional status of school going adolescent girls in semi urban area of West Bengal. This study was conducted among 746 school children of 11-18 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
2
6
0
1
Order By: Relevance
“…Low height-for-age among Limbu and Mech children and adolescents from two districts of West Bengal, India from Purba Medinipur district in south West Bengal also reported that 9 to 13 year-old Bengalee children of both sexes were suffering from stunting (14.6%) [6]. A study from semi-urban population of Hooghly district reported high prevalence of stunting (27%) among 11 to 18 yearold adolescent girls [10]. In Puruliya district of southwestern part of West Bengal, frequency of stunting was also high among 5 to 12 year old Santal boys (22%) and girls (14%) [21].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Low height-for-age among Limbu and Mech children and adolescents from two districts of West Bengal, India from Purba Medinipur district in south West Bengal also reported that 9 to 13 year-old Bengalee children of both sexes were suffering from stunting (14.6%) [6]. A study from semi-urban population of Hooghly district reported high prevalence of stunting (27%) among 11 to 18 yearold adolescent girls [10]. In Puruliya district of southwestern part of West Bengal, frequency of stunting was also high among 5 to 12 year old Santal boys (22%) and girls (14%) [21].…”
Section: Discussionmentioning
confidence: 95%
“…A report from 116 school going adolescents (aged 10-19 years) of Periurban area of Wardha, Pune from western province of India shows poor nutritional status of adolescents including 34.5% stunting where boys are found to be suffering more (72.5%) than girls (27.5%) [4]. From eastern India, studies among children and adolescents reported high degree stunting [5,6,7,8,9,10,11]. Other studies from Aligarh, north India [12], Gujarat, western India [13] and Andhra Pradesh from South India [14] also reported high prevalence of stunting in children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“… 10 In contrast, it was lower (34.0%) compared with the research conducted in Bangladesh. 21 Indonesia (25.0%), 22 rural India (19.2%), 23 West Bengal in India (20.7%) and (31.4%), 24 , 25 and various regions of Ethiopia 9 , 10 , 12–16 , 26–29 are among the countries with the highest percentages. These disparities could have a long-term nutritional influence on school-aged adolescent girls due to seasonal variance, economic condition, and educational attainment of the families.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the prevalence of overweight and obesity (14.5%) is slightly higher. In comparison, undernutrition (18.9%) is grossly lower than the estimated values used to calculate the sample size for the study from the literature review [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The prevalence of thinness was also found to be much less than NFHS-4 (2015-2016).…”
Section: Discussionmentioning
confidence: 99%
“…Malnutrition still remains a serious health problem among adolescents in India, especially among girls, despite the implementation of several programs and schemes like Rashtriya Kishor Swasthya Karyakram (RKSK), Rajiv Gandhi Scheme for Empowerment of Adolescent Girls (RGSEAG Sabla), Integrated Child Development Services (ICDS), Prime Minister's Overarching Scheme for Holistic Nourishment (POSHAN) Abhiyaan with importance to adolescent health [1,[3][4][5]. It has been found that the prevalence of thinness among adolescent girls in urban India ranged from 15% to 74%, while that of being overweight was about 8% to 13%, primarily due to the varied standards of assessment of nutritional status across different studies [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. National Family Health Survey-4 (NFHS-4) states that in the age group of 15-19 years, 41.9% of girls were undernourished, and 4.2% of girls were overweight or obese [21].…”
Section: Introductionmentioning
confidence: 99%